Implementing Problem-Based Learning to Improve Advanced Reading Skills Among Students with Learning Difficulties - Yunisa, Riya; Sukinah, Sukinah (Papanda Publisher, 2025)
This classroom action research investigated the effectiveness of Problem-Based Learning (PBL) in improving advanced reading skills among fifth-grade students with learning difficulties. Seven students at SDN A Muara Bengkal who scored below minimum competency criteria (KKM=70) participated in this study. The research employed Kemmis and McTaggart's cyclical model across two complete intervention cycles, incorporating pre- and post-assessments, systematic observations, and teacher interviews. Data analysis utilized both quantitative methods (descriptive statistics and percentage improvements) and qualitative approaches (thematic analysis of observations and interviews). Results demonstrated substantial improvement in reading achievement, with mean scores increasing from 47.14 at baseline to 63.57 after Cycle I and 72.14 after Cycle II, representing a total gain of 25 points. Five of seven students (71%) achieved or exceeded competency standards, with notable enhancements in critical thinking, collaborative engagement, and academic confidence. However, two students with severe reading disabilities showed minimal progress, indicating that PBL effectiveness varies based on individual learning profiles. The findings suggest that PBL serves as an effective pedagogical approach within multi-tiered inclusive education systems when implemented with culturally relevant content, differentiated scaffolding, and iterative refinement, though intensive individualized interventions remain necessary for students with profound learning difficulties.